2023
DOI: 10.1186/s13027-023-00553-4
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of HPV among 164,137 women in China exhibited some unique epidemiological characteristics

Qiong Chen,
Wanglei Qu,
Yu Zhao
et al.

Abstract: Objective The persistence of HPV infection is a significant etiological factor in the development of cervical cancer. The present study investigated the prevalence and genotype distribution of human papillomavirus (HPV) in a cohort of 164,137 unvaccinated women from Wenzhou, aiming to provide guidance for clinics in the cervical cancer screening and HPV vaccination strategies. Methods The present retrospective study included a total of 164,137 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Comparative studies of the HPV distribution in patients with genital warts of both sexes in the Asia-Pacific region are limited, with even fewer reports from China. At present, researches on the distribution of HPV in China mainly focus on the female population ( Chen et al, 2023 ; Wei et al, 2023 ; Zhang et al, 2023 ); Research on the distribution of HPV among general warts is commonly found in northern China ( Zhu C. et al, 2019 ). HPV infection is mainly transmitted between male and female, and the distribution of HPV also has regional characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies of the HPV distribution in patients with genital warts of both sexes in the Asia-Pacific region are limited, with even fewer reports from China. At present, researches on the distribution of HPV in China mainly focus on the female population ( Chen et al, 2023 ; Wei et al, 2023 ; Zhang et al, 2023 ); Research on the distribution of HPV among general warts is commonly found in northern China ( Zhu C. et al, 2019 ). HPV infection is mainly transmitted between male and female, and the distribution of HPV also has regional characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, age [ 75 ], geographic origin [ 76 ], sexual behavior [ 77 ], and HPV vaccination [ 78 ] might interact with HPV prevalence and thus influence high-grade cervical disease development. HPV infection was not detected in one CIN 2+ patient, which implies that other potential confounding factors might contribute in this patient’s cervical lesion.…”
Section: Discussionmentioning
confidence: 99%